2009
DOI: 10.5194/acpd-9-24051-2009
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mercury emission and speciation of coal-fired power plants in China

Abstract: Abstract. Comprehensive field measurements are needed to understand the mercury emissions from Chinese power plants and to improve the accuracy of emission inventories. Characterization of mercury emissions and their behavior were measured in six typical coal-fired power plants in China. During the tests, the flue gas was sampled simultaneously at inlet and outlet of selective catalyst reduction (SCR), electrostatic precipitators (ESP), and flue gas desulfurization (FGD) using the Ontario Hydro Method (OHM). T… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 24 publications
0
48
0
Order By: Relevance
“…Several emission tests on-site measurement of Hg in process streams and flue gases of coal-fired power plants equipped with various types of emission control devices have been conducted in China Tang et al, 2007;Zhang et al, 2008;Wang et al, 2010). In Guizhou province, statistical data for coal consumption suggested that large-scale coal-fired power plants, industrial boilers, and domestic users consumed about 30%, 48%, and 22% of the total, respectively .…”
Section: Mercury Emissionmentioning
confidence: 99%
“…Several emission tests on-site measurement of Hg in process streams and flue gases of coal-fired power plants equipped with various types of emission control devices have been conducted in China Tang et al, 2007;Zhang et al, 2008;Wang et al, 2010). In Guizhou province, statistical data for coal consumption suggested that large-scale coal-fired power plants, industrial boilers, and domestic users consumed about 30%, 48%, and 22% of the total, respectively .…”
Section: Mercury Emissionmentioning
confidence: 99%
“…Speciation depends on chemical composition of combusted coal. In coals with higher chlorine, bromine or other halogen content share of oxidized mercury increases (Zhang et al, 2008;Wang et al, 2009;Wang et al, 2010;Buitrago, 2011). Salts containing these elements decompose during combustion to HCl, HBr and HI and further to Cl 2 , Br 2 and I 2 .…”
Section: Mercury Emission Potentialmentioning
confidence: 99%
“…For 4 coal mines with highest Hg/Cl factor (from 0.00056 to 0.0008) the potential of mercury emission is significant. High mercury content and relatively low content of chlorine and bromine causes domination of reduced Hg 0 form, which will not be eliminated during dedusting and desulfurization processes (Galbreath & Zygarlicke, 2000;Wang et al, 2010;Chmielniak et al, 2010). …”
Section: Mercury Emission Potentialmentioning
confidence: 99%
See 2 more Smart Citations